Preliminary Study on Immediate Postoperative CT Images and Values of the Modular Polyetheretherketone Based Total Knee Arthroplasty: An Observational First-in-Human Trial - Cai, Zhengyu; Qu, Xinhua; Zhao, Yaochao; Yuan, Zhiguo; Zheng, Liangjun; Long, Teng; Yao, Qiuying; Yue, Bing; Wang, You (Frontiers in Surgery, 2022)
Abstract Background: Total knee arthroplasty (TKA) is now frequently performed and is highly successful. However, patient satisfaction after TKA is often difficult to achieve. Because of the presence of metallic prosthetic knee joints, there is a lack of imaging tools that can accurately assess the patient’s postoperative prosthetic position, soft tissue impingement, and periprosthetic bone density after TKA. We conducted a clinical trial of the world’s first totally modular polyetheretherketone (PEEK) TKA and determined the bone density values in the stress concentration area around the prosthesis based on postoperative computed tomography data to reconstruct a three-dimensional model of the PEEK prosthetic knee joint after implantation. Based on the model, the overhang of the prosthesis was measured at various locations on the prosthesis. Methods: All patients who underwent PEEK-based TKA were postoperatively assessed with radiography and computed tomography (CT). Hounsfield units (HUs) for the different components of the quantitative CT assessment were measured separately. Results: Ten patients (nine female and one male) aged 59 to 74 (mean 66.9, median 67) years were included. The HU values were as follows: PEEK prosthesis mean 186.61, standard deviation (SD) 7.78, coefficient of variation (CV) -4.63; polyethylene mean -89.41, SD 4.14, CV 4.63; lateral femoral osteochondral mean 192.19, SD 55.05, CV 28.64; lateral tibial osteochondral mean 144.99, SD 62.14, CV 42.86; medial femoral osteophyte mean 180.76, SD 43.48, CV 24.05; and medial tibial osteophyte mean 282.59, SD 69.28, CV 24.52. There was no overhang in all femoral prostheses, whereas there were two cases of overhang in tibial prostheses. Conclusion: PEEK knee joint prosthesis has excellent CT compatibility. The change in periprosthetic bone volume during the follow-up period can be determined using the HU value after CT scan, while the prosthesis position can be assessed. This assessment may potentially guide future improvements in knee prosthesis alignment techniques and artificial knee prosthesis designs. Trial registration: ClinicalTrials.gov (NCT04927104)